Adolescent and Young Adult Urogenital Outcome following Childhood Hypospadias Repair: Perfection Revisited. Issue 3 (6th September 2021) - Tack, Lloyd J. W.; Springer, Alexander; Riedl, Stefan; Tonnhofer, Ursula; Hiess, Manuela; Weninger, Julia; Mahmoud, Ahmed; Van Laecke, Erik; Hoebeke, Piet; Cools, Martine; Spinoit, Anne-Françoise
Abstract : Purpose: We assessed the long-term surgical, functional urinary and sexual outcomes of adolescent and young adult men who underwent childhood hypospadias repair. Materials and Methods: Men born with nonsyndromic hypospadias and healthy male controls aged 16–21 years old were recruited, and their surgical, urinary, sexual functional and aesthetic outcomes assessed. Good outcome was defined as a patent and orthotopic meatus without fistulas, and straight erections (<30 degree curvature) without erectile or ejaculatory problems. Statistics included regression analyses, chi-square/Fisher exact tests and Student's t/Mann-Whitney U and Kruskal-Wallis tests. Results: A total of 193 patients and 50 controls participated 16.4 years (range 8.2–21.2) after initial repair. At least 1 reintervention was performed in 39.2%. The highest reintervention rate was found in those younger than 12 months at initial repair, even when excluding proximal hypospadias cases. A disturbed urinary and/or suboptimal sexual functional outcome was seen in 52.9% of cases. Suboptimal voiding was found in 22.1%, although few had relevant residual urine. More reinterventions and proximal hypospadias cases were associated with suboptimal urinary outcome, and the latter also with impaired sexual function. Poor inter-observer agreements were found between physician and patient genital appraisal. Conclusions: In 52.9% of cases, at least 1 concern was identified that required long-term followup. Hypospadias repair below 12 months was associated with more reinterventions. Adopting a restrictive attitude toward aesthetic refinement, unless on the patient's own request, could improve urinary outcomes.